Antibody responses to yellow fever vaccine in 9 to 11-month-old Malian and Ghanaian children. (3rd August 2019) - Idoko, Olubukola T.; Mohammed, Nuredin; Ansah, Patrick; Hodgson, Abraham; Tapia, Milagritos D.; Sow, Samba O.; Chowdhury, Paanchali R.; Niedrig, Matthias; Saathoff, Elmar; Kampmann, Beate
ABSTRACT: Background : The World Health Organization recommends use of a single yellow fever (YF) vaccine dose for life and fractional doses in outbreaks when there are limited vaccine stocks. In endemic regions, this vaccine is given as part of routine infant immunization programs around 9 months of age. There is a need to better understand immune responses when vaccinating infants particularly in contexts where the child may be malnourished. Methods : Data from 393 Malian and Ghanaian infants who concomitantly received measles and YF vaccines at 9 to 11 months of age were retrospectively analyzed. Response to YF vaccine was examined for association with nutritional status at time of vaccination, sex, age, pre-vaccination titers and season of vaccination. Results : Neutralizing antibodies following vaccination were unaffected by season of vaccination, sex, pre-vaccination titers or nutritional status, though there was a trend to higher titers in males and children with higher height for age z-scores. Seroconversion rates differed significantly between countries (63.5 in Ghana vs. 91.0% in Mali). Conclusion : Longitudinal, prospective studies are needed to optimize the use of YF vaccine in infants in endemic settings. There may be a need for booster vaccinations and to compare various vaccine preparations to optimize the use of available vaccines.